Potential of Small Molecules Piperidine and Pyrrolidine Against Copper-Resistant Xanthomonas perforans, Causal Agent of Bacterial Spot of Tomato - Pierre, Ketsira (Plant disease, 2024)
Bacterial spot of tomato (BST), caused by Xanthomonas perforans, is an economically important disease of tomatoes in Florida. Due to the heavy reliance on copper-based bactericides for control of BST, copper-resistant strains of X. perforans are widely distributed in Florida, leading to reduced efficacy of copper-based bactericides for disease control. There is a need for alternative chemical control strategies to effectively manage this disease in tomato production. In this study, two small molecules, piperidine and pyrrolidine, were evaluated for their efficacy against the copper-resistant X. perforans strain GEV 485 in laboratory, greenhouse, and field experiments. In in vitro experiments, piperidine and pyrrolidine at concentrations as low as 2 mg/L and 16 mg/L, respectively, significantly (P<0.001) reduced bacterial populations within 4 h of incubation compared to the untreated control, while Kocide 3000, the grower copper-based bactericide standard, at 0.9 g/L and 2.1 g/L (full label rate) did not significantly reduce bacterial populations. When tested as foliar sprays in the greenhouse, pyrrolidine at 128 mg/L significantly (P <0.001) reduced disease severity compared to the untreated control, with an equivalent efficacy to Kocide 3000 (copper hydroxide at 2.1 g/L). Kocide 3000 at 1.0 g/L, in combination with piperidine at 64 mg/L and pyrrolidine at 64 and 128 mg/L significantly improved the efficacy in disease control compared to untreated controls and Kocide 3000 at 1.0 g/L alone. In field trials, both small molecules demonstrated equivalent or superior efficacy to ManKocide (copper hydroxide + mancozeb) against X. perforans compared to the untreated control. This study demonstrated for the first time the potential of piperidine and pyrrolidine for controlling bacterial spot of tomato